Utility of prior cultures in predicting antibiotic resistance of bloodstream infections due to Gram-negative pathogens: a multicentre observational cohort study. (May 2018) - MacFadden, D.R.; Coburn, B.; Shah, N.; Robicsek, A.; Savage, R.; Elligsen, M.; Daneman, N.
Abstract: Objectives: Appropriate empiric antibiotic therapy in patients with bloodstream infections due to Gram-negative pathogens can improve outcomes. We evaluated the utility of prior microbiologic results for guiding empiric treatment in Gram-negative bloodstream infections. Methods: We conducted a multicentre observational cohort study in two large health systems in Canada and the United States, including 1832 hospitalized patients with Gram-negative bloodstream infection (community, hospital and intensive care unit acquired) from April 2010 to March 2015. Results: Among 1832 patients with Gram-negative bloodstream infection, 28% ( n  = 504) of patients had a documented prior Gram-negative organism from a nonscreening culture within the previous 12 months. A most recent prior Gram-negative organism resistant to a given antibiotic was strongly predictive of the current organism's resistance to the same antibiotic. The overall specificity was 0.92 (95% confidence interval (CI) 0.91–0.93), and positive predictive value was 0.66 (95% CI 0.61–0.70) for predicting antibiotic resistance. Specificities and positive predictive values ranged from 0.77 to 0.98 and 0.43 to 0.78, respectively, across different antibiotics, organisms and patient subgroups. Increasing time between cultures was associated with a decrease in positive predictive value but not specificity. An heuristic based on a prior resistant Gram-negative pathogen could have been applied to one in four patients and in these patients would have changed therapy in one in five. Conclusions: In patients with a bloodstream infection with a Gram-negative organism, identification of a most recent prior Gram-negative organism resistant to a drug of interest (within the last 12 months) is highly specific for resistance and should preclude use of that antibiotic.